2003
DOI: 10.1162/003465303765299828
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Pricing in a Regulated Market

Abstract: We compare how new pharmaceuticals are priced in the price-regulated Swedish market with how they are priced in the U.S. market, as studied by Lu and Comanor (1998). We collect a data set consisting of all new chemical entities (NCEs) launched in Sweden between 1987 and 1997, and test the same models as Lu and Comanor. In line with their results, we find that introductory prices depend on the degree of therapeutic innovation. Contrary to the results from the U.S. market, Swedish real prices for NCEs fall subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 9 publications
2
58
0
4
Order By: Relevance
“…Thus, given that price increases are uncommon, the NHS compensates the producers with a relatively high introductory price as Ekelund and Persson (2003) found for the Swedish market. In other words, the regulation of prices impedes penetration strategies, i.e., entry into the market with low prices.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, given that price increases are uncommon, the NHS compensates the producers with a relatively high introductory price as Ekelund and Persson (2003) found for the Swedish market. In other words, the regulation of prices impedes penetration strategies, i.e., entry into the market with low prices.…”
Section: Discussionmentioning
confidence: 92%
“…A study by Lou and Commanor in the US showed that launch prices for new drugs were related to therapeutic value (Lu and Comanor, 1998). Also in the Swedish markets with price control on pharmaceutical, initial pricing is related to value (Ekelund and Persson, 2003). However, recently there has been further studies on pricing for new cancer drugs mainly paid by private and public insurers, .…”
Section: Introductionmentioning
confidence: 99%
“…The empirical literature has focused on both the pricing strategies of originators postpatent expiration (Frank and Salkever, 1992, Scherer, 1993, Regan, 2008 as well as on prices of the follow-on and generics (Lu and Comanor, 1998, Ekelund and Persson, 2003, Danzon and Furukawa, 2011, Mueller and Frenzel, 2015. There is a large literature on price discrimination (third degree) and welfare effects (Scherer, 2000, Danzon, 1997, Malueg and Schwartz, 1994 and when in the presence of heterogeneous consumers firms can profitably divide the market in different brand loyal and not-brand loyal groups via advertising to achieve second degree price discrimination (de Frutos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%